2018
DOI: 10.1016/j.ijmedinf.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of telephone nursing on healthcare utilization

Abstract: We present a robust Bayesian ordinal regression model that predicts three-quarters of the patients' healthcare utilization after telephone nursing and we found no evidence of model deficiencies. A patient's compliance to the nurse's recommendation varies and depends on the recommended level of care, its agreement with and level of the patient's prior intention, and the availability of different care options at the time. The model reveals a risk reducing behavior among patients and the effect of the telephone n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The most valuable and relevant new evidence is from research that has started to investigate the more complex patient and system factors that can explain variation and behaviours. There is an emerging theme about the important relationships between caller expectations, intended action, attitudes to risk, agreement with triage decision and subsequent satisfaction and utilisation of services, 26,27,38,39 together with environmental factors such as rurality and deprivation, 22,23 all of which need to be considered as part of service design. There are interesting developments about how patient-reported characteristics, such as degree of worry, might be incorporated into triage questioning 31,40 and about the effect of language proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most valuable and relevant new evidence is from research that has started to investigate the more complex patient and system factors that can explain variation and behaviours. There is an emerging theme about the important relationships between caller expectations, intended action, attitudes to risk, agreement with triage decision and subsequent satisfaction and utilisation of services, 26,27,38,39 together with environmental factors such as rurality and deprivation, 22,23 all of which need to be considered as part of service design. There are interesting developments about how patient-reported characteristics, such as degree of worry, might be incorporated into triage questioning 31,40 and about the effect of language proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The level of care advised, the extent to which advice agreed with the caller's prior intention, care option availability and perceptions of risk also have an effect, with compliance seven times higher if the highest level of care is advised. 26 One paper 27 investigated the effect of English-language proficiency and found that those with limited proficiency were less likely (60.9%) to follow advice than those who were proficient (69.4%) and were more likely to have a higher level of care disposition.…”
Section: Compliancementioning
confidence: 99%
See 2 more Smart Citations
“…Finally, callers may have chosen not to follow the recommendations because they lacked confidence in the telenurse or found the recommendations inappropriate. 20 36 37 …”
Section: Discussionmentioning
confidence: 99%